Electronic structure, spectroscopy and photophysics of rubidium mono-sulphide - Mehnen, Bilel; Akkari, Sana; Zrafi, Wissem; Jendoubi, Ibtissem; Bejaoui, Mohamed; Bulut, Niyazi; Hochlaf, Majdi (Pergamon-Elsevier Science Ltd, 2024)
We investigated the nineteen first electronic states of the RbS diatomic using post Hartree-Fock configuration interaction methods at the internally contracted multi -reference configuration interaction (MRCI +(Q)) level. We thus mapped their respective potential energy curves with and without considering spin -orbit effects. After nuclear motion treatments, we derived their equilibrium distances, rotational and vibrational constants, and dissociation and electronic excitation energies. Moreover, an evaluation of the dipole moments of RbS was conducted, which in turn were used to evaluate the radiative lifetimes of the vibrational levels of RbS (X 2 & Pcy; and A 2 Sigma + ) states. Computations show that spin -orbit interactions are important and cannot be omitted. Afterwards, and utilizing the sum rule approximation and the Franck - Condon factors, we computed both the bound -bound contributions and the bound -free terms. Our findings suggest that RbS exhibits intriguing characteristics suitable for laser cooling experiments. In sum, this work contributes to the understanding in-depth of the spectroscopy of RbS and predicts its use as a promising molecular system for laser cooling applications.
Keywords: Rubidium mono-sulphide; RbS; Ab initio computations; Vibrational levels; Radiative lifetimes; Spin orbit; Laser cooling